Впровадження інноваційних засобів медико-психологічної реабілітації військовослужбовців зони ато у провідних країнах світу та в Україні = Implementation of innovative medical and psychological rehabilitation servicepersons zone ato in leading countries and in Ukraine - Sadova, M. A.; Sоkоlоvskiy, R. V.; Nіzаmutdіnоv, I. Ph. (Journal of Education, Health and Sport, 2016)
Sadova М. А., Sоkоlоvskiy R. V., Nіzаmutdіnоv І. Ph. Впровадження інноваційних засобів медико-психологічної реабілітації військовослужбовців зони ато у провідних країнах світу та в Україні = Implementation of innovative medical and psychological rehabilitation servicepersons zone ato in leading countries and in Ukraine. Journal of Education, Health and Sport. 2016;6(7):27-34. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56848 http://ojs.ukw.edu.pl/index.php/johs/article/view/3654 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. УДК 159.923.2:001.8 ВПРОВАДЖЕННЯ ІННОВАЦІЙНИХ ЗАСОБІВ МЕДИКО-ПСИХОЛОГІЧНОЇ РЕАБІЛІТАЦІЇ ВІЙСЬКОВОСЛУЖБОВЦІВ ЗОНИ АТО У ПРОВІДНИХ КРАЇНАХ СВІТУ ТА В УКРАЇНІ М. А. Садова, Р. В. Соколовський, І. Ф. Нізамутдінов Науково-дослідний центр Збройних Сил України «Державний океанаріум» Реферат Стаття розглядає проблему інноваційних засобів в медико-психологічній реабілітації, зокрема таких як, індивідуальна психотерапія, групова психотерапія, сімейна психотерапія, подружня психотерапія, соціально-історична корекція. Ці методи та техніки застосовуються при лікуванні психологічних та соматичних розладах військовослужбовців зони ведення бойових дій як в провідних країнах світу так і в Україні. Ключові слова: інноваційні засоби, медико-психологічна реабілітація, індивідуальна психотерапія, групова психотерапія, подружня психотерапія, соціально-історична корекція. Implementation of innovative medical and psychological rehabilitation SERVICEPERSONS ZONE ATO in leading countries and in UKRAINE М. А. Sadova, R. V. Sоkоlоvskiy, І. Ph. Nіzаmutdіnоv Research Center of the Armed Forces of Ukraine "State Oceanarium" Аbstract The article considers the problem inovatiynih funds for medical and psychological rehabilitation, including such as individual psychotherapy, group therapy, family therapy, marital therapy, socio-historical correction. These methods and techniques are used in the treatment of psychological and somatic disorders military warfare zone in the leading countries of the world and in Ukraine. Keywords: innovative tools, medical and psychological rehabilitation, individual psychotherapy, group therapy, marital therapy, socio-historical correction. ВНЕДРЕНИЕ ИННОВАЦИОННЫХ СПОСОБОВ МЕДИКО-ПСИХОЛОГИЧЕСКОЙ РЕАБИЛИТАЦИИ ВОЕННОСЛУЖАЩИХ ЗОНЫ АТО В ВЕДУЩИХ СТРАНАХ МИРА И В УКРАИНЕ М. А. Садовая, Р. В. Соколовский, И. Ф. Низамутдинов Научно-исследовательский центр Вооруженных Сил Украини «Государственный океанариум» Реферат Статья рассматривает проблему иноватийних средств в медико-психологической реабилитации, в том числе таких как, индивидуальная психотерапия, групповая психотерапия, семейная психотерапия, супружеская психотерапия, социально-историческая коррекция. Эти методы и техники применяются при лечении психологических и соматических расстройствах военнослужащих зоны ведения боевых действий как в ведущих странах мира так и в Украине. Ключевые слова: инновационные средства, медико-психологическая реабилитация, индивидуальная психотерапия, групповая психотерапия, супружеская психотерапия, социально-историческая коррекция.